A Qualitative Study on Requirements Engineering Practices in an Artificial Intelligence Unit of the Brazilian Industrial Research and Innovation Company - Martins, Mariana Crisostomo; Kudo, Taciana Novo; Bulcão-Neto, Renato F. (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2024)
In recent years, there has been a focus shift from software development in general to the construction and training of machine learning (ML) models integrated into a software product. This movement has raised challenges in ML systems’ requirements engineering (RE) theory and practice. This paper investigates RE practices in ML systems research, development, and innovation projects carried out by an Artificial Intelligence (AI) Unit of the Brazilian Industrial Research and Innovation Company. Our methodology includes semi-structured interviews with leaders of 21 projects and data analysis through the grounded theory method. We identified the predominance of RE methods, techniques, and tools applied ad hoc and uncoordinatedly. This result corroborates the literature reports on RE for ML systems, especially those involving innovation projects.